2007
DOI: 10.1111/j.1365-277x.2007.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of serum biochemical indicators in anorexia nervosa patients: a 1‐year follow‐up study

Abstract: Background Long-term studies on the evolution of serum biochemical indicators in anorexia nervosa (AN) patients during treatment are lacking in the literature. Thus, a 1-year follow-up of serum biochemical parameters in a homogeneous group of AN patients was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
2
23
1
3
Order By: Relevance
“…41 Other proposed uses of Arg include also improvement of cardiovascular circulation and renal blood flow. 42 In addition, as hypercholesterolaemia is a common finding in patients with AN, [43][44][45][46] in line with our work, the abnormal lipid profile (increased total cholesterol and LDL-cholesterol levels) is associated with an elevated risk for arteriosclerotic diseases, 46 and in this regards Arg supplementation might be an useful tool in vascular health.…”
Section: Discussionsupporting
confidence: 85%
“…41 Other proposed uses of Arg include also improvement of cardiovascular circulation and renal blood flow. 42 In addition, as hypercholesterolaemia is a common finding in patients with AN, [43][44][45][46] in line with our work, the abnormal lipid profile (increased total cholesterol and LDL-cholesterol levels) is associated with an elevated risk for arteriosclerotic diseases, 46 and in this regards Arg supplementation might be an useful tool in vascular health.…”
Section: Discussionsupporting
confidence: 85%
“…Some authors also showed that T-chol, HDL-chol, and LDLchol were higher in AN patients than in healthy subjects as indicators of severe malnourishment (28,29). On the other hand, Nova et al (30) reported that AST was significantly lower in AN patients compared with healthy subjects. However, the AST value was within the normal range in the present study because of the possible adaptive mechanisms that preserve liver function until advanced stages of debilitation such as seen in AN patients (31).…”
Section: Discussionmentioning
confidence: 93%
“…Studies reveal conflicting results, with some studies showing elevations of AST and others showing low levels of AST 40,41 Both may be possible. An increase of AST is seen in any condition involving necrosis of hepatocytes, myocardial cells, or skeletal muscle cells.…”
Section: Liver Enzymesmentioning
confidence: 95%